ANTIBACTERIAL ACTIVITIES OF BELIMBING WULUH (AVERRHOA BILIMBI L.) ETHYL ACETATE EXTRACT ON GEL FORMULATED AGAINST PROPIONIBACTERIUM ACNES AND STAPHYLOCOCCUS AUREUS - PERTIWI, DEWI; HAFIZ, IHSANUL; JANNAH, WARDATUL; WINATA, HANAFIS SASTRA; SARI, MELIA; SUROYO, RAZIA BEGUM (International Journal of Applied Pharmaceutics, 2020)
Objective: Averrhoa bilimbi is a plant that is used as a food spice and traditional medicine in Indonesia. The purpose of this study was to obtain a gel formula and measure its activity in inhibiting the growth of skin bacteria, namely Propionibacterium acnes and Staphylococcus aureus. Methods: The gel formulation was tested organoleptically, homogeneity, pH, dispersibility test, and skin irritation test. Antibacterial activity test using agar diffusion method, inhibition of bacterial growth was compared with clindamycin as a positive control. Results: All gel formulations showed good homogeneity, pH of the preparations ranged from 4.5 to 6.1, the dispersion test was 5.5-6.5 cm, and none of them caused irritation to the skin. The results of the inhibitory activity against the growth of Propionibacterium acnes bacteria on concentrations 10, 15, and 20% were 16.67 + 0.40, 22.70 + 0.32 and 28.10 + 0.36 and Staphylococcus aureus bacteria were 18.53 + 0.22, 24.16 + 0.29 and 30.40 + 0.4. The inhibitory activity of clindamycin against Propionibacterium acnes and Staphylococcus aureus bacteria were 35.33+0.29 and 36.30+0.37. Conclusion: Ethyl acetate extract gel Averrhoa bilimbi had good activity in inhibiting the growth of Propionibacterium acnes and Staphylococcus aureus bacteria and has the potential to be used as an herbal anti-acne drug.